2019
DOI: 10.1016/j.enganabound.2019.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating the fictitious frequency problem in BEM solutions of the external Helmholtz equation

Abstract: The problem of the fictitious frequency spectrum resulting from numerical implementations of the boundary element method for the exterior Helmholtz problem is revisited. When the ordinary 3D free space Green's function is replaced by a modified Green's function, it is shown that these fictitious frequencies do not necessarily have to correspond to the internal resonance frequency of the object. Together with a recently developed fully desingularized boundary element method that confers superior numerical accur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…It appears that, even with a very small interval of 0.001 for ka, we still missed many of the fictitious frequencies. This confirms the findings of [16,28], where it was found that for moderate ka values, the non-singular boundary element method is already quite good at avoiding non-physical solutions at fictitious frequencies.…”
Section: Scattering From a Rigid Cubesupporting
confidence: 89%
See 2 more Smart Citations
“…It appears that, even with a very small interval of 0.001 for ka, we still missed many of the fictitious frequencies. This confirms the findings of [16,28], where it was found that for moderate ka values, the non-singular boundary element method is already quite good at avoiding non-physical solutions at fictitious frequencies.…”
Section: Scattering From a Rigid Cubesupporting
confidence: 89%
“…Clearly, the non-physical solutions at the classical internal resonance frequencies show up in the curve for the non-singular standard boundary element method, for example, at ka = 9.356 and ka = 10.417, corresponding to the theoretical values of ka = 9.3558 and ka = 10.41712, respectively (see also Table 1 in Ref. [16]).…”
Section: Scattering From a Rigid Spherementioning
confidence: 93%
See 1 more Smart Citation
“…Since the desingularized boundary element method with high order elements, such as quadratic curved elements, is so accurate, a further advantage is that it is very unlikely to hit an internal resonance frequency (and get a so-called spurious solution), thus there is no need to apply Burton-Miller type of schemes (Burton and Miller, 1971). For a more elaborate discussion on the fictitious frequency problem see (Klaseboer et al, 2019). Also with the superior quadratic elements we only need a fraction of the nodes needed to get the same accuracy as with standard flat constant elements.…”
Section: Introductionmentioning
confidence: 99%
“…In fact with our desingularized boundary element method, the probability of hitting a spurious solution is actually very low. In fact, it is even difficult to find such a frequency when specifically looking for it (see the figures in [10]). The two most popular methods to deal with fictitious frequencies are the CHIEF method proposed by Schenck [23] and the Burton-Miller method [3].…”
mentioning
confidence: 99%